Pós tratamento por eletrocoagulação de efluente do processamento do soro de leite tratado por reator anaeróbio - Souza, Camila Favretto de (2021)
Whey is a by-product of cheese making, rich in lactose, protein and minerals and of economic importance. From the processing of whey, there remains an effluent to be treated, rich in organic matter and nutrients, which needs adequate treatment to minimize the environmental impacts of its release. Anaerobic treatment proves to be a good treatment alternative for this type of effluent due to its ability to remove organic matter, however, this treatment is not good at removing nutrients, requiring a complementary treatment. In this sense, electrocoagulation can be an alternative due to its capacity to reduce sludge volume and good removal of nutrients. Thus, the objective of this work is to evaluate whether electrocoagulation, as a method of anaerobic after-treatment of effluent generated in the processing of whey, is effective in removing COD and phosphorus. The present work evaluated the efficiency in the removal of organic charge and nutrients through the combination of anaerobic and electrolytic processes in the treatment of effluent from the processing of whey. In the treatment in anaerobic reactor, retention time of 3 and 10 days and temperatures of 15, 25 and 35ºC were used. The effluent treated from this process was sent for treatment in an electrolytic reactor, being studied the type of electrode (Iron and Aluminum), the treatment time (20 and 40 min) and the current density (0.5 and 1.0 A / m2). The anaerobic treatment proved to be efficient, obtaining removal greater than 99% in apparent color, 97% in turbidity and 98% in COD at temperatures of 25 and 35ºC for a period of 10 days. The same behavior was not observed in the removal of phosphorus, proving the need for post-treatment. The best COD removal was with an iron electrode reaching 91% and phosphorus with an aluminum electrode, obtaining 64% removal, demonstrating that the electrolytic treatment after anaerobic treatment is an efficient method of after treatment for the whey effluent.